Non-local theory of buckling of tapered nano columns under self weight and an axial tip load using matrix based Chebyshev spectral collocation (MBCSC) - Rajasekaran, S. (Journal of Structural Engineering, 2024)
In this paper, elastic buckling of tapered Euler Bernoulli nano columns for tip load and self weight using non-local theory of elasticity is studied using matrix based Chebyshev spectral collocation method (MBCSC). The size effect is taken into consideration using Eringen’s non-local elasticity theory. Detailed numerical analyses about the effects of boundary conditions and load types are conducted and the influence of non-local parameter on the static buckling response of tapered or uniform nano tubes and rods is discussed. It is hoped that the results in this paper may present a bench mark in the study of buckling of tapered nano rods and tubes.